Diaporthe eres causes stem cankers and death of young apple rootstocks in Canada. Issue 2 (2nd April 2020) - Ali, Shawkat; Renderos, Willy; Bevis, Eric; Hebb, Joan; Abbasi, Pervaiz A.
Abstract: In the spring of 2018, necrotic and canker symptoms were observed on stems of young apple trees that were bench-grafted by growers on four rootstocks (EMLA 9, Supporter 4, M9-T337 and Pajam 2) in Annapolis Valley, Nova Scotia. The objective of this study was to isolate and identify the causal organism of the disease on apple rootstocks. The diseased tissue obtained from eight infected plants of the four rootstocks showing visible necrotic and canker symptoms was used for microorganism isolation on potato dextrose agar (PDA). More than 90% of the isolates on PDA yielded a similar type of fungal colony. Based on the colony and spore morphology and presence of both α and β spores, Diaporthe was proposed as a major pathogen from the symptomatic tissue. Analysis of partial sequences of four unlinked loci DNA-lyase (APN2), histone-3 (HIS), translation elongation factor 1 alpha (TEF1-α) and the internal transcribed spacer (ITS) 5.8S region of rDNA of the representative fungal isolates from young apple trees confirmed its identity as D. eres ( Phomopsis fukushii ). The pathogenicity of the representative D. eres isolate was confirmed on 1-year-old young apple trees bench-grafted on four different rootstocks in greenhouse tests. Necrotic and sunken canker symptoms like those observed on the nursery-grown young apple trees appeared on stems of all inoculated plants. The necrotic and canker lesions were observed 3 days after inoculation; they spread both directions from the inoculation point and led to the death of the young plants after 4 weeks. To our knowledge, this is the first report of D. eres causing stem canker and death of young apple rootstock in Canada.